Efficient design of a radome for minimised transmission loss. Issue 15 (1st December 2016) - Sheret, Tamara; Parini, Clive; Allen, Ben
Abstract : A radome has to be carefully designed to ensure it has minimum impact on the performance of the antenna. Traditional approaches involve equation approximations, complex ray tracing, iterative manufacturing process and or electrically large and lengthy electromagnetic (EM) simulations. The novel approach described in this study involves a two‐dimensional ray tracing method simulation in MATLAB and an electrically small unit cell simulation in high‐frequency structure simulator. This new approach gives an optimal thickness result that is only 0.004 mm different to that of a full EM simulation. The radome is manufactured and radio‐frequency tested in an anechoic chamber, the calculated thickness is shown to be the optimal thickness.